2021
DOI: 10.1136/bjophthalmol-2020-317560
|View full text |Cite
|
Sign up to set email alerts
|

Extension study of the safety and efficacy of CLS-TA for treatment of macular oedema associated with non-infectious uveitis (MAGNOLIA)

Abstract: PurposeTo assess the extended efficacy and safety of suprachoroidal triamcinolone acetonide injectable suspension (CLS-TA) among patients with macular oedema (ME) secondary to non-infectious uveitis (NIU).MethodsPatients with uveitic ME were treated with suprachoroidal CLS-TA at baseline and week 12 of the Efficacy and Safety of Suprachoroidal CLS-TA for Macular Edema Secondary to Noninfectious Uveitis: Phase 3 Randomized Trial (PEACHTREE) study. Time to rescue was evaluated over 24 additional weeks for MAGNOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 5 publications
0
62
0
Order By: Relevance
“…This section focuses on the efficacy of SCS triamcinolone acetonide in the pivotal phase III PEACHTREE trial [ 15 ] and its extension (MAGNOLIA) [ 16 ]. SCS triamcinolone acetonide improved visual acuity in a phase I/II trial [ 17 ] and reduced central subfield thickness (CST) in a phase II trial (DOGWOOD) [ 18 ] in patients with macular edema due to non-infectious uveitis; these data are not discussed further.…”
Section: Therapeutic Efficacy Of Scs Triamcinolone Acetonidementioning
confidence: 99%
See 2 more Smart Citations
“…This section focuses on the efficacy of SCS triamcinolone acetonide in the pivotal phase III PEACHTREE trial [ 15 ] and its extension (MAGNOLIA) [ 16 ]. SCS triamcinolone acetonide improved visual acuity in a phase I/II trial [ 17 ] and reduced central subfield thickness (CST) in a phase II trial (DOGWOOD) [ 18 ] in patients with macular edema due to non-infectious uveitis; these data are not discussed further.…”
Section: Therapeutic Efficacy Of Scs Triamcinolone Acetonidementioning
confidence: 99%
“…Patients from selected centers completing PEACHTREE without requiring rescue therapy were enrolled in MAGNOLIA for an additional 24 weeks’ follow-up ( n = 28 in the SCS triamcinolone acetonide and 5 in the sham group) with no further treatment [ 16 ]. The primary endpoint of MAGNOLIA was time to rescue therapy from the date of first study treatment administration in PEACHTREE.…”
Section: Therapeutic Efficacy Of Scs Triamcinolone Acetonidementioning
confidence: 99%
See 1 more Smart Citation
“…The study enrolled 33 eyes—28 CLS-TA and 5 control. The median time to rescue therapy was 257 versus 55.5 days in the treatment and control groups, respectively, and approximately 50% of treated patients did not require additional therapy up to 9 months following last CLS-TA administration [ 76 ].…”
Section: Pharmacotherapies In Human Clinical Trialsmentioning
confidence: 99%
“…Much like the preclinical studies, minimal systemic absorption was found [ 60 ]. In the most recent phase III trials, the suprachoroidal injection resulted in a significant reduction in macular edema and visual improvement compared to sham injections [ 30 , 61 ]. The injection has been marketed to target and treat macular edema; however, there is hope that this new method could be another approach to treating posterior segment inflammation but with a lower side effect profile than other steroid-based therapies.…”
Section: Local Therapymentioning
confidence: 99%